Kinetics of the Release of Platelet-Derived Growth Factor (PDGF-BB) Derived from Human Umbilical Cord: Cinética de la liberación del factor de crecimiento derivado de plaquetas (PDGF-BB) en plasma - Aro Guardia, Pedro Alberto (2024)
Introduction: The use of cord blood (UC) offers numerous advantages in regenerative medicine. Platelet-rich plasma (PRP) is a source of growth factors where its dynamics over time have been evaluated in peripheral blood; however, its evaluation in UC blood has not been studied. Objective: To evaluate the kinetics of PDGF-BB release from PRP obtained from UC blood. Materials and methods: In vitro experimental study. UC blood samples were collected from 6 term deliveries of healthy pregnant women between 18 and 36 years of age who attended the Cayetano Heredia Hospital in Lima-Peru. The samples obtained were centrifuged at 900 g for 10 minutes to prepare the PRP. Activation was performed with 10% calcium gluconate (GLu.Ca) and divided into 4 aliquots: (i) without activator; (ii) 1 hour; (iii) 24 hours; (iv) 48 hours. PDGF-BB quantification was evaluated by ELISA method. Results: The mean ± standard deviation of PDGF-BB concentration measured at 1 hour, 24 hours and 48 hours were 6127.9 ± 101.6, 6197.5 ± 34 and 6176.8 ± 63.3 respectively. The kinetics of PDGF-BB released by PRP showed constant values during the 48 hours. Conclusions: PDGF-BB release from PRP obtained from UC blood was rapidly induced and remained constant and sustained during the first 48 hours after activation.